2022
DOI: 10.1007/s00198-022-06460-5
|View full text |Cite
|
Sign up to set email alerts
|

A micro-costing analysis of post-fracture care pathways: results from the International Costs and Utilities Related to Osteoporotic Fractures Study (ICUROS)

Abstract: Summary This study identified the costs and health-related quality of life impacts of several post-fracture multidisciplinary care pathways specific to individual skeletal site (hip, distal forearm, vertebrae, humerus). These care pathways may assist healthcare providers in allocating resources for osteoporotic fractures in more effective and cost-efficient ways. Introduction This micro-costing study was undertaken to provide the estimated healthcare costs of several fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In HICs, the same systematic review and meta-regression analysis reported the total health and social care costs in the 12 months following HF to be U$50,540 (95% CI; US$36,372-64,707), adjusted for inflation to 2021 prices. More recently, Talevski et al [30] reported a mean cost per patient in class 6 HF care pathway (the model we considered to have close similarities to HF care as provided in KZN public hospitals) of $48,999 (95% CI; 39,704-58,294) Australian Dollars [approximately US$30,387 (95% CI; 24,622-36,151)]. Healthcare resource utilization and costs following fractures reflect the pathways of care.…”
Section: Discussionmentioning
confidence: 98%
“…In HICs, the same systematic review and meta-regression analysis reported the total health and social care costs in the 12 months following HF to be U$50,540 (95% CI; US$36,372-64,707), adjusted for inflation to 2021 prices. More recently, Talevski et al [30] reported a mean cost per patient in class 6 HF care pathway (the model we considered to have close similarities to HF care as provided in KZN public hospitals) of $48,999 (95% CI; 39,704-58,294) Australian Dollars [approximately US$30,387 (95% CI; 24,622-36,151)]. Healthcare resource utilization and costs following fractures reflect the pathways of care.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have mostly been concerned and reported that smoking increases the risk of hip fracture 11 , 12 . However, the osteoporosis questionnaires in NHANES focus not only on hip fractures but also on wrist and spine fractures, which are common complications of osteoporosis 22 , 23 . In our current study, we performed a comprehensive study of smoking and osteoporotic fractures of the hip, wrist, and spine using the NHANES database, indicating that smoking raised the risk of these types of fractures.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with most previous economic evaluations that estimated the long-term costs of hip fracture based on admission rates to nursing homes following the fracture, this study used yearly incremental costs of hip, vertebral, and NHNV during a 5-year post-fracture follow-up period, according to the same study of Tran et al [ 15 ]. As hip fractures are associated with long-term admission to nursing home and costs [ 30 ], the incremental cost of hip fractures in year 5 from Tran et al was maintained for a lifetime. No cost after the 5-year period was conservatively assumed for vertebral and NHNV fractures (except in a sensitivity analysis).…”
Section: Methodsmentioning
confidence: 99%